Visual and auditory attention defects in children with intermittent exotropia - Cong Wei; Ding-Ping Yang; Yan Yang; Wen-Han Yang; Ya-Mei Lu; Xin-Ping Yu; Shuai Chang (BMC, 2024)
Abstract Background Previous studies have shown that children with intermittent exotropia (IXT) have a higher rate of psychiatric abnormalities as they grow up, such as attention deficit. This study explored visual and hearing attention among children with IXT, and evaluated its association with clinical characteristics and cognitive development. Methods Forty-nine children with a diagnosis of IXT and 29 children with traditional development were recruited. The Integrated Visual and Auditory Continuous Performance Test (IVA-CPT) was used to measure the subjects' full-scale response control quotient (FSRCQ), full-scale attention quotient (FSAQ), auditory response control quotient (ARCQ), auditory attention quotient (AAQ), visual response control quotient (VRCQ), and visual attention quotient (VAQ). The Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV) was used to assess their cognitive function. The differences between the scores of children with IXT and normal controls were analyzed. Results The results showed that the FSRCQ, FSAQ, ARCQ, AAQ, VRCQ, and VAQ of children with IXT were all lower than those of normal controls with the same age (P < 0.05). The level of attention was significantly correlated with the age of strabismus onset (P < 0.05), but not with the degree of strabismus, stereopsis, or fusion control score. In addition, audiovisual attention was correlated significantly with their cognitive development level. The random forest classifier prediction model showed that age of strabismus onset was an important predictor of attention. Conclusion Children with IXT have lower visual and auditory attention and control than their peers, and the age of onset of strabismus may be a major factor.